2008
DOI: 10.1177/0142723707087583
|View full text |Cite
|
Sign up to set email alerts
|

Gestures accompanying speech in specifically language-impaired children and their timing with speech

Abstract: The repertoire and timing of gestures accompanying speech were compared in children with specific language impairment (SLI), aged 5-10 years, in typically developing peers (CA), individually matched on age and nonverbal IQ, and in younger language-matched (LM) children. They were videotaped in two tasks, recounting a cartoon and describing their classroom. Three types of gestures were coded -iconics, deictics and beats -and the synchrony of these gestures with speech was examined in terms of number of words en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 33 publications
(40 reference statements)
8
50
0
8
Order By: Relevance
“…For example, young children sometimes achieve more complex communicative ‘utterances’ first by using a ‘speech+gesture’ strategy (e.g. mummy+ball gesture to indicate ‘mummy give me the ball’) and this has also been shown to be the case in gestures accompanying speech in children with SLI (Blake, Myszczyszyn, Jokel, & Bebiroglu, 2008). But by 28 months children prefer verbal to gestural expression, expecting a spoken label to reference objects and their categories (Namy & Waxman, 1998).…”
Section: Gesture In Typical Developmentmentioning
confidence: 99%
“…For example, young children sometimes achieve more complex communicative ‘utterances’ first by using a ‘speech+gesture’ strategy (e.g. mummy+ball gesture to indicate ‘mummy give me the ball’) and this has also been shown to be the case in gestures accompanying speech in children with SLI (Blake, Myszczyszyn, Jokel, & Bebiroglu, 2008). But by 28 months children prefer verbal to gestural expression, expecting a spoken label to reference objects and their categories (Namy & Waxman, 1998).…”
Section: Gesture In Typical Developmentmentioning
confidence: 99%
“…Both Blake et al . () and Iverson and Braddock (), who examined gestures produced in narrative tasks, observed that children with SLI produced more representational gestures in the absence of words than did their TD peers. However, Iverson and Braddock did not find significant group differences in gestures that provided additional or disambiguating content.…”
Section: Introductionmentioning
confidence: 99%
“…In another study Blake et al . () asked participants to perform cartoon retell and classroom description tasks. A majority of the observed gestures were representational, but there was no significant difference in the frequency of representational gestures produced by children with SLI and their TD peers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations